Kontestasi Retorika Islam Nusantara - Safitri, Dini (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2017)
This study aims to describe the contestation of Islamic Nusantara rhetoric in Social Media between two Islamic organizations in Indonesia. The first mass organization was NU as the creator of Islam Nusantara idea and HTI as the repudiation of Islam Nusantara idea. To obtain the description, the researchers used the theory of Gramsi to analyze the text contained in the official web of NU and HTI on Islam Nusantara. The results show that there is contestation between NU and HTI in producing Islamic Nusantara rhetoric in New Media. NU as the largest Islamic organization in Indonesia feels the need to develop the Islamic Nusantara model as a distinctive feature of Islam in Indonesia against the hegemony of radical Islamic values entering Indonesia. The intellectual elite of NU is also widely revealed in its text on the official web of NU, that radical Islamic values are also carried by other Islamic organizations such as HTI which is the international Islamic organization of the Middle East. Meanwhile, HTI elites also produce texts to reject Islam Nusantara because Islam is only one, and invites the Islamic community of Indonesia not to be divided. Penelitian ini bertujuan untuk mengambarkan kontestasi retorika Islam Nusantara di Media Sosial antara dua ormas Islam di Indonesia. Ormas pertama adalah NU sebagai pengusung gagasan Islam Nusantara dan HTI sebagai penolak gagasan Islam Nusantara. Untuk memperoleh gambaran tersebut, peneliti memakai teori dari Gramsi untuk menganalisa teks yang dimuat dalam web resmi NU dan HTI mengenai Islam Nusantara. Hasil penelitian menunjukan terdapat kontestasi antara NU dan HTI dalam memproduksi retorika Islam Nusantara di Media Baru. NU sebagai ormas Islam terbesar di Indonesia merasa perlu melakukan pengembangan model Islam Nusantara sebagai ciri khas dari Islam di Indonesia untuk melawan hegemoni dari nilai-nilai Islam radikal yang tengah memasuki Indonesia. Elit intelektual NU juga banyak mengungkapkan dalam teksnya di web resmi NU, bahwa nilai-nilai Islam radikal tersebut juga dibawa oleh ormas islam lain seperti HTI yang merupakan organisasi islam internasional dari Timur Tengah. Sementara itu, elit HTI juga memproduksi teks untuk menolak Islam Nusantara dikarenakan Islam itu hanya satu, dan mengajak masyarakat Islam Indonesia untuk tidak terpecah-belah